2014
DOI: 10.4056/sigs.5779977
|View full text |Cite
|
Sign up to set email alerts
|

Complete genome sequence of Kosakonia sacchari type strain SP1T

Abstract: Kosakonia sacchari sp. nov. is a new species within the new genus Kosakonia, which was included in the genus Enterobacter. K sacchari is a nitrogen-fixing bacterium named for its association with sugarcane (Saccharum officinarum L.). K sacchari bacteria are Gram-negative, aerobic, non-spore-forming, motile rods. Strain SP1T (=CGMCC1.12102T=LMG 26783T) is the type strain of the K sacchari sp. nov and is able to colonize and fix N2 in association with sugarcane plants, thus promoting plant growth. Here we summar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 19 publications
1
25
0
Order By: Relevance
“…The increasing cell densities observed between the different root regions indicate that K. sacchari proliferated along the growing root. The strain used in this study is very closely related to type strain K. sacchari SP1 T (99.89% 16S rRNA sequence identity, Chen et al, 2014), a heterotrophic bacterium that has been reported to colonize sugarcane plants and to exhibit plantgrowth promotion through nitrogen fixation. In this study, the dense colonization of all observed regions indicates that carbon substrates provided by the plant (i.e., the necessary food source for K. sacchari in our experimental system) may not only have been available at the root tip but also at the elongation zone, as well was in the zone of maturity.…”
Section: Bacterial Cell Distributions On Rootsmentioning
confidence: 99%
“…The increasing cell densities observed between the different root regions indicate that K. sacchari proliferated along the growing root. The strain used in this study is very closely related to type strain K. sacchari SP1 T (99.89% 16S rRNA sequence identity, Chen et al, 2014), a heterotrophic bacterium that has been reported to colonize sugarcane plants and to exhibit plantgrowth promotion through nitrogen fixation. In this study, the dense colonization of all observed regions indicates that carbon substrates provided by the plant (i.e., the necessary food source for K. sacchari in our experimental system) may not only have been available at the root tip but also at the elongation zone, as well was in the zone of maturity.…”
Section: Bacterial Cell Distributions On Rootsmentioning
confidence: 99%
“…Kosakonia sacchari (formerly known as Enterobacter sacchari) is a Gram-negative aerobic diazotrophic bacterium belonging to the class of Gammaproteobacteria [27]. An endo polygalacturonase gene was reported in the complete genome sequence of K. sacchari strain BO-1 (NZ_CP016337.1).…”
Section: Discussionmentioning
confidence: 99%
“…Kosakonia sacchari was isolated, identified and proved to cause potato soft rot [18]. On the other hand, Kosakonia sacchari was isolated as a nitrogen fixing bacteria that colonize sugar cane promoting its growth [26].…”
Section: Discussionmentioning
confidence: 99%